IMPLEMENTATION OF DIGITAL MARKETING AT PT FRATAMA KENCANA GEMILANG - Wikah Widiyawati; Citra Savitri; Syifa Pramudita Faddila (SEAN Institute, 2022)
The development of information technology that is growing very rapidly has an effect on the community in supporting various business activities, both large and small so that they can be known globally. The marketing trend is switching from conventional (offline) to digital (online). The concept of digital marketing for business actors1 is to be able to market their products from anywhere and anytime via the internet. The focus of the problem raised is the application of digital marketing. This study uses a type of qualitative research that is useful for providing facts and data regarding the application of digital marketing. Then data collection techniques using interview techniques. From the results of the study, it was found that PT Fratama Kencana Gemilang felt the benefits of digital marketing such as more affordable promotional costs, being able to reach wider consumers, more complete information content and more accurate data. However, the most felt benefit by carrying out promotional activities using digital marketing is that it can reach wider consumers throughout Indonesia.